Implementasi Program Corporate Social Responsibility (CSR) Pada Pt. Furama Villa And Spa Ubud - I Gusti Ngurah Agung; I Nyoman Putu Budiartha; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2020)
Abstract-Corporate social responsibility activities or other terms called CSR are corporate obligations where companies are required to be responsible for operational activities in the field of natural resources; CSR is regulated in article 74 of Law No. 40 of 2007 of the Company Law concerning social and environmental responsibilities. In the hotel and service operational activities of PT. Furama Villa and Spa Ubud, located in the village of Mekar Bhuana, Banjar Bindu, Badung certainly has a positive and negative impact on the economic, social, cultural and environmental aspects. As for the discussion to be discussed, among others; 1. What is the CSR Program at PT. Furama Villa and Spa Ubud, 2. What are the Implications in the CSR Program at PT Furama Villa and Spa Ubud. This research is an empirical research which is analyzed qualitatively descriptive. Data obtained through interviews with parties involved in CSR activities. Implementation of CSR at PT. Furama has been committed to giving donations to people with disabilities, elementary school scholarships that have ranked I to V and preserving nature by making agro farms. In its implications, the implementation of CSR in companies arises from several aspects, namely: the economy opens up employment opportunities while increasing people's living standards, socially creates positive emotions of the community and companies, and environmentally participates in preserving nature by planting trees and making agro farm. Keywords: CSR, Villa, Tourism Abstrak-Kegiatan tanggung jawab social perusahaan atau istilah lainnya disebut CSR merupakan kewajiban perusahaan dimana perusahaan dituntut untuk bertanggung jawab atas aktivitas oprasional yang kegiatannya di bidang sumber daya alam, CSR diatur dalam pasal 74 Undang-Undang Nomor 40 tahun 2007 UUPT tentang tanggung jawab sosial dan lingkungan. Di dalam Kegiatan oprasional hotel maupun jasa PT. Furama Villa and Spa Ubud yang berlokasi di Desa Mekar Bhuana, Banjar Bindu, Badung tentu menimbulkan dampak positif dan negatif dalam sektor ekonomi, sosial budaya, lingkungan sekitar. Adapun pembahasan yang akan dibahas antara lain ; 1. Bagaimanakah Program CSR pada PT.Furama Villa and spa Ubud, 2. Bagaimanakah Implikasi dalam Program CSR pada PT Furama Villa and Spa ubud. Penelitian ini merupakan penelitian Empiris yang dianalisis secara kualitatif deskriptif. Data yang diperoleh melalui wawancara dengan pihak yang terlibat dalam kegiatan CSR. Adapun penerapan CSR pada PT. Furama sudah dilakukan berkomitmen dengan dilakukannya pemberian sumbangan terhadap penyandang cacat, beasiswa SD yang berprestasi peringkat I sampai V dan melestarikan alam dengan membuat agrofarm. Dalam implikasinya penerapan CSR dalam perusahaan timbul dari beberapa aspek yaitu; ekonomi membuka lapangan pekerjaan sekaligus meningkatkan taraf hidup masyarakat, sosial terjalinnya emosi positif masyarakat dan perusahaan, lingkungan ikut serta menjaga kelestarian alam dengan menanam pohon dan membuat agrofam. Kata Kunci: CSR, Villa, Pariwisata